Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 1 - Review: 51

Answer

a. 15

Work Step by Step

Substitute 3, -6, and -9 for x, y, and z and solve the expression. 2$x^{2}$ - y + z = 2$(3^{2})$ - (-6) + (-9) = 2(9) - (-6) + (-9) = 18 - (-6) + (-9) = 24 + (-9) = 15
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.